Antiliberalismo e autoritarismo nos escritos de Carl Schmitt (1919-1933) - Costa, Alencar Cardoso da (2016)
The study object of this dissertation is the writings produced by Carl Schmitt between the years of the Weimar Republic (1919-1933). Our historical subject was a lawyer and political scientist, considered the greatest German jurist of the twentieth century. This jurist developed hundreds of works such as articles, books and essays. He was devoted to the branch of jurisprudence, became interested in Public Law and International Law. He performed works that comprise the fields of law, philosophy and political science. His thought, clipping analyzed time, was marked by an illiberal and authoritarian stance. Drawing inspiration from the ideas of counterrevolutionary authors, and Donoso Cortés the main one. Also owned inspired by the works of the English thinker Thomas Hobbes. The intellectual history of Carl Schmitt is stigmatized for their involvement in National Socialism, and is affiliated with the National Socialist German Workers Party (NSDAP) in 1933. However, in 1936 eventually moving away from official party cadres. Carl Schmitt advocated the formation of a strong, centralized government, as opposed to what he called "weak", "anachronistic" and "depoliticized" parliamentary government of the Weimar Republic. He believed that the sovereign power could be exercised by a leader who contained in himself the general will of the people.